Designing with uncertainty: a form behaviour approach to behavioural scientific studies - Tümtürk, Onur (AESOP, 2017)
The expeditious rise of the Modernism discourse -and its contributions on the architecture and urban design theory and practice at the beginning of the 20th century -has given much of its place to harsh criticisms and brand-new questions in the following years. According to Lang (1987), major developments arising from the Modern Movement such as unprecedented growth in human knowledge, major social changes, and increase in the standard of living made design praxis difficult rather than making it easier. Lang legitimizes this speculative and critical point of view with the assertion of having the technological ability to construct buildings, neighbourhoods, and cities in a wide variety of ways without fully understanding the ramifications of designing for human behaviour. Within this critical approach, after mid-1900s a new field of environmental studies – generalized as behavioural sciences -has emerged in the context of man and environment relationship which deals with the complex systematic interactions between the people and built environment.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017